Dual enzymatic dynamic kinetic resolution by Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase and Candida antarctica lipase B. Issue 99 (10th October 2016) - Karume, Ibrahim; Musa, Musa M.; Bsharat, Odey; Takahashi, Masateru; Hamdan, Samir M.; El Ali, Bassam
Abstract : The immobilization of Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase (TeSADH) using sol–gel method enables its use to racemize enantiopure alcohols in organic media, thus allows for a dual enzymatic dynamic kinetic resolution. Abstract : The immobilization of Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase (TeSADH) using sol–gel method enables its use to racemize enantiopure alcohols in organic media. Here, we report the racemization of enantiopure phenyl-ring-containing secondary alcohols using xerogel-immobilized W110A TeSADH in hexane rather than the aqueous medium required by the enzyme. We further showed that this racemization approach in organic solvent was compatible with Candida antarctica lipase B (CALB)-catalyzed kinetic resolution. This compatibility, therefore, allowed a dual enzymatic dynamic kinetic resolution of racemic alcohols using CALB-catalyzed kinetic resolution and W110A TeSADH-catalyzed racemization of phenyl-ring-containing alcohols.